Photodynamics of clusters of the major components of the atmosphere. (2004) - Aquilanti, V.; Bartolomei, M.; Cappelletti, D.; Carmona-Novillo, E.; Pirani, F.
Abstract : Weakly interacting molecules leading to collisional complexes, and to either stable or metastable dimers, potentially play an important role in molecular and surface physics, in astrophysics, in atmospheric photochemistry and physics, and climate. Accurate intermolecular potential energy surfaces for the major components of the atmosphere, leading to the characterization of theO 2 -O 2, N 2 -N 2 andN 2 -O 2 dimers, have been obtained from the analysis of scattering experiments from our laboratory, also exploiting where available second virial coefficient data. A spherical harmonic expansion functional form describes the geometries of the dimers and accounts for the relative contributions to the intermolecular interaction from components of different nature. ForO 2 -O 2, singlet, triplet and quintet surfaces are obtained accounting for the role of spin-spin coupling. The new surfaces allow the full characterization of structure and internal dynamics of the clusters, whose bound states and eigenfunctions are obtained by exact quantum mechanics. Besides the information on the nature of the bond, these results can be of use in modelling the role of dimers in air and the calculated rotovibrational levels provide a guidance for the analysis of spectra, thus establishing the ground for atmospheric monitorings. Reference is also briefly made to recent insight on the role of water.